Analysis of the Effect of Budget Participation on Budgetary Slack: Study Literature Review - Devi Pertiwi Ananda Putri; Sri Trisnaningsih (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine how budget participation affects budgetary slack. Using data sources from Mendeley, Publish or Perish 8, and Google Scholar indexed by Sinta 1-6, Google Scholar, Garuda, or EBSCO and Index Copernicus, as well as credible international journals indexed by Scopus throughout a five-year period beginning in 2019–2024, this study employs the System Literature Review approach. The search terms